Musculoskeletal Injuries among ERCP Endoscopists in Canada. (2002) - O'Sullivan, Sinead; Bridge, Gary; Ponich, Terry
Abstract : BACKGROUND: There are few reports in the literature describing musculoskeletal complaints among endoscopists, and none are specific to those who perform endoscopic retrograde cholangiopancreatography (ERCP). PURPOSE: To examine the current practices of ERCP endoscopists and the prevalence of musculoskeletal injuries. METHODS: A self-report survey was sent to physicians practising ERCP across Canada identified through a pre-existing database. A second mailing was sent six weeks later to those who did not respond to the first mailing. RESULTS: Of 162 surveys sent, 122 responses were received, with five respondents indicating that they no longer performed ERCP and three declining to participate. Of the 114 participants, 67% reported at least one musculoskeletal complaint, and 58% reported two or more complaints. Seventy-four per cent attributed their symptoms to endoscopy and/or ERCP, and 79% reported that their condition was aggravated by performing ERCP. The most frequently reported pain symptoms were back pain (57%), neck pain (46%) and hand pain (33%), which are all consistent with the physical risks involved in performing ERCP. Only 51% reported taking regular breaks, and only 25% reported having fluoroscopy tables with adjustable heights. The room designs of the respondents' ERCP facilities were analyzed for ergonomic considerations: 67% had poor ergonomics and 33% had good ergonomics. Sixty-four per cent reported that they were interested in learning preventive strategies. CONCLUSIONS: Physicians who perform ERCP develop musculoskeletal injuries and are interested in learning about risk factor modification.